The Effect of Inequality of Income, Per Capita Income, and Government Expenditures in the Health Area on the Health Sector in Indonesia - Hasanah, Uswatun; Ahmadi, H (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2017)
Human resource is one of capital importance in the development of a nation. One of the important aspects that affect human resources is the public health level, where the health sector has an important role. The status of one's health is the result of the interaction of various factors, namely internal and external factors. Internal factors consist of physical and psychological factors, while external factors consist of economic factors, education, environment and culture. This research aims to examine and analyze the effect of income inequality as measured by the Gini Ratio against the health sector as measured by life expectancy in Indonesia in 2005-2013. On the research of regression equation using data panels with Random Effects Model approach. The results of this research are the inequality of income, per capita income, and Government expenditure in the health effect simultaneously against health sector in Indonesia in 2005-2013 and are partial, inequality of income, per capita income, and Government expenditure in the health sector impact health sector in Indonesia in 2005-2013.